Penerapan Bermain Teka-Teki Silang dalam Meningkatkan Kecerdasan Linguistik Anak Usia 5-6 Tahun - Nanda, Nadya Octa (Jambura Early Childhood Education Journal, 2023)
Linguistic intelligence is the ability to use words correctly. The purpose of this study is to find out how the application of playing crossword puzzles improves linguistic intelligence in children aged 5-6 years at TK Harapan Bangsa in Bulu China Village. The research method used in this research is classroom action research. The results of the study found that playing crossword puzzles can improve children's linguistic intelligence. The results of the assessment before the action was carried out obtained an average value of 40.42%. In cycle I it increased by 52.92%, then in cycle II the achievement of children's linguistic development increased by 81.71%. Therefore, from the results of the analysis that has been carried out, there has been an increase both individually and in groups starting from pre-action, cycle I then cycle II. The increase in linguistic intelligence can be seen from the presentation of assessment scores in the instrument before the action, cycle I and cycle II, namely from 40.42% before the action, cycle I was 52.92% and cycle II was 81.71%.